THE ROLE OF TEACHERS AS AGENTS OF SOCIALIZATION IN THE INTERNALIZATION OF JAVANESE CULTURAL VALUES THROUGH THE EDUCATIONAL PRACTICE OF TRADITIONAL SNACK EXHIBITIONS AND CULTURAL ARTS PERFORMANCES - Wijaya, Dimas Putra (Journal on Research and Review of Educational Innovation, 2025)
This qualitative case study is motivated by concerns regarding the erosion of Javanese cultural values due to globalization and the influence of technology impacting Generation Z. The research aims to understand the strategic role of teachers as socialization agents in internalizing these values through the Traditional Snack Exhibition and Cultural Arts Performance at SDI Ma'arif, Blitar City. The method used is qualitative case study, with data collection techniques employing participatory observation, in-depth interviews, and document analysis. The results reveal four teacher roles: (1) as Contextual Designer, (2) Participatory Facilitator, (3) Role Model, and (4) Reflection Partner. The process of internalizing values such as mutual cooperation, respect, and harmony occurs through the dynamic stages of Transformation, Transaction, and Transinternalization. This confirms that the effectiveness of character education heavily relies on the teacher's ability to design authentic and meaningful experiential learning. Therefore, this culture-based practice is recommended as an integrated model to strengthen students' cultural resilience.